Water stability and frost resistance clay strengthening stabilizer, preparation method and application thereof

By using organic cationic polymers, cationic surfactants, fluorosilane-modified polyurethane silicone composite hollow nanomicrospheres and high-performance mineral-based gelling materials in clay, the protective film and hydrophobic layer are formed, which solves the problem of unstable waterproof and frost resistance of clay, and significantly improves its water stability and frost resistance.

CN118993597BActive Publication Date: 2025-04-01JIANGSU GUOLU ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411079337.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2025-04-01
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

In the prior art, the waterproof and freezing resistance of clay are unstable, resulting in the gradually weakening of its effect during long-term use and insufficient durability.

Method used

Combination technology of organic cationic polymers, cationic surfactants, fluorosilane modified polyurethane silicone composite hollow nanomicrospheres and high-performance mineral-based gelling materials is used to form a protective film and a hydrophobic layer to improve the water stability and frost resistance of the clay.

Benefits of technology

It effectively prevents the hydration, expansion and dispersion of clay minerals, improves the waterproofness, frost resistance and stability of clay, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004983268190000121
    Figure BDA0004983268190000121
  • Figure BDA0004983268190000131
    Figure BDA0004983268190000131
Patent Text Reader

Abstract

The present application discloses a water-stable and frost-resistant clay strengthening stabilizer, a preparation method and its application, and relates to the technical field of clay strengthening stabilizers. The raw materials of the clay strengthening stabilizer include 2-4 parts of organic cationic polymers, 8-12 parts of cationic surfactants, 6-10 parts of fluorosilane-modified polyurethane silicone composite hollow nano-microspheres, and 0.8-2 parts of high-performance mineral-based gelling materials by weight; the mass ratio of the organic cationic polymer to the cationic surfactant is 1: (3-5); the cationic surfactant is one of hexadecyl trimethyl ammonium bromide, coconut oil alkyl trimethyl ammonium chloride, and dodecyl trimethyl ammonium bromide; the raw materials of the organic cationic polymer include acrylamide, methacryloyloxyethyl trimethyl ammonium chloride, and an initiator. The clay strengthening stabilizer provided in the present application can significantly improve the water stability and frost resistance of clay.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of clay strengthening stabilizer technology, and in particular to a water-stable and frost-resistant clay strengthening stabilizer, a preparation method and an application thereof. Background Art

[0002] Clay is a natural material composed of fine particles, usually a mixture of water and minerals (such as silicates, oxides, etc.), and its microscopic form is mainly fine particles and layered chain structures. Clay has the characteristics of viscosity, plasticity and adsorption, and is widely used in construction, ceramics, agriculture, medicine and other fields.

[0003] Clay minerals are mainly composed of kaolinite, montmorillonite, illite and chlorite. Montmorillonite is an expansive clay mineral with a large number of exchangeable cations inside. Once montmorillonite encounters water, water molecules will enter the crystal layer. The exchangeable cations will dissociate in water, making the clay mineral crystal layer negatively charged. The crystal layers repel each other, and the distance between the crystal layers increases, causing the clay to expand. This is also the reason for the deterioration of many roadbeds / road layers.

[0004] In the prior art, polymer emulsions, silicate waterproofing agents, etc. are often added to clay materials to fill the gaps between clay particles to form a protective layer to reduce water penetration, thereby improving its anti-penetration performance; or adding an appropriate amount of organic matter to improve the drainage performance of clay, but the effect of these waterproofing agents will gradually weaken over time, resulting in unstable waterproof and antifreeze capabilities of clay and insufficient durability. Therefore, it is urgent to provide a new clay strengthening stabilizer to improve the water stability and antifreeze properties of clay. Summary of the invention

[0005] In order to improve the water stability and frost resistance of clay, the present application provides a water stability and frost resistance clay strengthening stabilizer, a preparation method and application thereof.

[0006] The water-stable and frost-resistant clay strengthening stabilizer provided in this application adopts the following technical scheme:

[0007] A water-stable and frost-resistant clay strengthening stabilizer, wherein the raw materials include, by weight, 2-4 parts of an organic cationic polymer, 8-12 parts of a cationic surfactant, 6-10 parts of fluorosilane-modified polyurethane organic silicon composite hollow nano-microspheres, and 0.8-2 parts of a high-performance mineral-based gelling material; the mass ratio of the organic cationic polymer to the cationic surfactant is 1:(3-5).

[0008] By adopting the above technical scheme, the positively charged atoms on the cationic chain of the organic cationic polymer are used to exchange ions with ions on the clay particles, and the positively charged ions on the molecular chain are strongly attracted to the negative charges on the surface of the clay mineral, so that the organic cationic polymer is tightly adhered to the surface of the clay mineral and forms a protective film. The combination of the positively charged ions and the negative charges on the surface of the clay mineral maintains the charge balance on the one hand, and the cationic polymer can adhere to each tiny clay particle at the same time on the other hand, effectively preventing the hydration expansion and dispersion migration of the clay mineral, and can keep the clay stable for a long time. After the cationic surfactant is dissolved in water, it will ionize a large number of cations, which can neutralize the negative charge on the surface of the clay mineral and maintain the charge balance; and it can adhere to the clay mineral by hydrogen bonds and intermolecular forces, forming a hydrophobic and lipophilic layer, isolating water from the outside, and effectively preventing the hydration expansion and dispersion migration of the clay mineral; and the cationic surfactant can weaken the interaction between the clay particles and the modifier particles, thereby effectively dispersing the material, preventing agglomeration, and further enhancing the stability of the clay performance. Fluorosilane-modified polyurethane silicone composite hollow nano-microspheres have special surface structures and properties, which can make clay form a super-hydrophobic surface, so that water droplets present a high contact angle on the surface, thereby reducing the contact between water and clay particles and achieving a super-hydrophobic effect. High-performance mineral-based cementitious materials have high compressive strength, tensile strength and freeze-thaw resistance, which can make clay have more stable and lasting antifreeze properties. The combination of organic cationic polymers, cationic surfactants, fluorosilane-modified silicone nano-microspheres, and high-performance mineral-based cementitious materials as clay modifiers effectively improves the waterproofness, frost resistance and stability of clay.

[0009] Preferably, the cationic surfactant is one of cetyltrimethylammonium bromide, coconut oil alkyltrimethylammonium chloride and dodecyltrimethylammonium bromide.

[0010] Preferably, the raw materials of the organic cationic polymer include acrylamide, methacryloyloxyethyl trimethyl ammonium chloride, and an initiator, wherein the molar ratio of acrylamide to methacryloyloxyethyl trimethyl ammonium chloride is (1.8-2.2):1.

[0011] By adopting the above technical scheme, the organic cationic polymer formed by using acrylamide and methacryloyloxyethyltrimethylammonium chloride as raw materials under the action of an initiator has the effect of effectively improving the water stability of clay and preventing the clay from swelling.

[0012] Preferably, the initiator is ammonium persulfate, and the content of the initiator is 1%-2%.

[0013] The preparation method of the water-stable and frost-resistant clay strengthening stabilizer provided in the present application adopts the following technical scheme:

[0014] The preparation method of a water-stable and frost-resistant clay strengthening stabilizer comprises the following steps:

[0015] The organic cationic polymer, the cationic surfactant, the fluorosilane-modified organic silicon nano-microspheres and the high-performance mineral-based gelling material are weighed in parts by weight, mixed and stirred evenly to obtain a clay reinforcing stabilizer.

[0016] Preferably, the method for preparing the organic cationic polymer comprises the following steps:

[0017] Weigh acrylamide, methacryloyloxyethyl trimethyl ammonium chloride and initiator; mix acrylamide and methacryloyloxyethyl trimethyl ammonium chloride and stir them evenly, introduce nitrogen, heat to 55-65° C., and continue stirring; dissolve the initiator in water to obtain an initiator solution, then add the initiator solution dropwise to the reaction solution, continue the reaction for 6-8 hours, and obtain a crude product; wash and dry the crude product to obtain an organic cationic polymer.

[0018] Preferably, the method for preparing the fluorosilane-modified polyurethane organosilicon composite hollow nanospheres comprises the following steps:

[0019] Fluorosilane and ethanol are mixed at a volume ratio of 1:(10-11) to obtain an ethanol solution of fluorosilane; 0.3-0.5 parts of polyurethane silicone composite nano-microspheres are dispersed in a mixed solution of ethanol and water, and after ultrasonic dispersion, the temperature is raised to 60-70°C, and ammonia water is added. After 5-7 minutes, an ethanol solution containing 0.1-0.3 mL of fluorosilane is slowly added dropwise, and after reacting for 3-4 hours, ammonia water is added again, and the reaction is continued for 10-14 hours. The product is obtained by centrifugation, and after alternate centrifugation with ethanol and water, it is vacuum dried at 50-60°C for 20-30 hours to obtain fluorosilane-modified polyurethane silicone composite hollow nano-microspheres.

[0020] By adopting the above technical solution, the polyurethane silicone composite nano-microspheres are modified with fluorosilane, which not only improves the hydrophobicity of the polyurethane silicone composite nano-microspheres, but also etches the surface of the polyurethane silicone composite nano-microspheres with fluorosilane to form a hollow structure of the polyurethane silicone composite nano-microspheres, which can provide a larger specific surface area and more reactive sites, thereby effectively enhancing the hydrophobicity.

[0021] Preferably, the fluorosilane is perfluorooctyltriethoxysilane.

[0022] Preferably, the method for preparing the polyurethane-silicone composite nanospheres comprises the following steps:

[0023] S1. 5-7 parts of polycarbonate diol are stirred and dehydrated at 100-120 ° C under vacuum conditions for 2-3h, nitrogen is introduced, 0.6-0.8 parts of dimethylol propionic acid are added, stirred for 25-35min, cooled to 40-50 ° C, 2.5-3.5 parts of toluene diisocyanate and 0.005-0.007 parts of catalyst are added, and stirred at a constant temperature of 80-90 ° C for 2-3h to obtain a polyurethane dispersion;

[0024] S2. Add a mixed solution of ethanol and water in a volume ratio of (7-9): (10-12) to the polyurethane dispersion obtained in S1, and after uniform ultrasonic dispersion, continue stirring for 1-2 hours, then heat to 50-60°C, add NaOH solution, stir evenly, add 0.6-0.8L of vinyltriethoxysilane, react for 3-5 hours, obtain a precipitate by centrifugation, wash it with ethanol and water alternately by centrifugation, and vacuum dry it at 50-60°C for 20-30 hours to obtain polyurethane silicone composite nanospheres.

[0025] The present application also provides the use of a water-stable and frost-resistant clay reinforcing stabilizer, wherein the clay reinforcing stabilizer is used for preparing unfired clay bricks.

[0026] In summary, the present application includes at least one of the following beneficial technical effects:

[0027] 1. Organic cationic polymers strongly attract the negative charges on the surface of clay minerals through the positively charged ions on the molecular chain, so that the organic cationic polymers adhere tightly to the surface of clay minerals and form a protective film, which effectively prevents the hydration expansion and dispersion migration of clay minerals and can maintain the stability of clay for a long time.

[0028] 2. Cationic surfactants can neutralize the negative charge on the surface of clay minerals and maintain charge balance; they can also adhere to clay minerals using hydrogen bonds and intermolecular forces, forming a hydrophobic and lipophilic layer that isolates water and effectively prevents the hydration, expansion, dispersion and migration of clay minerals.

[0029] 3. Fluorosilane-modified polyurethane silicone composite hollow nano-microspheres have special surface structures and properties, which can make clay form a super-hydrophobic surface, so that water droplets present a high contact angle on the surface, thereby reducing the contact between water and clay particles and achieving a super-hydrophobic effect.

[0030] 4. High-performance mineral-based cementitious materials have high compressive strength, tensile strength and freeze-thaw resistance, which can make clay have more stable and lasting anti-freeze properties. DETAILED DESCRIPTION

[0031] The present application is further described in detail below with reference to the embodiments.

[0032] The chemical reagents used in the preparation examples, embodiments and comparative examples provided by the present invention are all commercially available products, and their brands and manufacturers are as follows:

[0033] Acrylamide, A800660, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0034] Methacryloyloxyethyltrimethylammonium chloride, 767502, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0035] Ammonium persulfate, A801034, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0036] Polycarbonate diol, Guangdong Wengjiang Chemical Reagent Co., Ltd.;

[0037] Dimethylolpropionic acid, B802228, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0038] Toluene diisocyanate, T823849, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0039] Dibutyltin dilaurate, D806313, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0040] Perfluorooctyltriethoxysilane, Hubei Xinmingtai Chemical Co., Ltd.;

[0041] Vinyltriethoxysilane, Hubei Xinmingtai Chemical Co., Ltd.;

[0042] Hexadecyltrimethylammonium bromide, PA00188, Guangdong Wengjiang Chemical Reagent Co., Ltd.;

[0043] Coconut oil alkyl trimethyl ammonium chloride, Suzhou Weidu Chemical Co., Ltd.;

[0044] Dodecyltrimethylammonium bromide, D806846, Shanghai MacLean Biochemical Technology Co., Ltd.

[0045] Preparation Example

[0046] Preparation Example 1 Preparation of organic cationic polymer

[0047] Preparation Example 1.1

[0048] Weigh 5 g of acrylamide, 3.08 g of methacryloyloxyethyl trimethyl ammonium chloride, and 0.0081 g of initiator ammonium persulfate; mix acrylamide and methacryloyloxyethyl trimethyl ammonium chloride at 300 rpm and stir evenly, introduce nitrogen for 1 hour, then heat to 55° C., and continue stirring to react; dissolve the initiator ammonium persulfate in 10 g of water to obtain an initiator solution, then add the initiator solution dropwise to the reaction solution, continue the reaction for 6 hours, and obtain a crude product; repeatedly wash the crude product with an ethanol / acetone mixture with a volume ratio of 2:1 until the washed liquid is clear, and then dry the product in a vacuum drying oven at 70° C. for 72 hours to obtain an organic cationic polymer.

[0049] Preparation Example 1.2

[0050] Weigh 5 g of acrylamide, 3.422 g of methacryloyloxyethyltrimethylammonium chloride, and 0.017 g of initiator ammonium persulfate; mix acrylamide and methacryloyloxyethyltrimethylammonium chloride and stir evenly at 350 rpm, introduce nitrogen for 1 hour, then heat to 60°C and continue stirring to react; dissolve the initiator ammonium persulfate in 13 g of water to obtain an initiator solution, then add the initiator solution dropwise to the reaction solution, continue the reaction for 6 hours, and obtain a crude product; repeatedly wash the crude product with an ethanol / acetone mixture with a volume ratio of 2:1 until the washed liquid is clear, and then dry the product in a vacuum drying oven at 70°C for 72 hours to obtain an organic cationic polymer.

[0051] Preparation Example 1.3

[0052] Weigh 5 g of acrylamide, 3.764 g of methacryloyloxyethyl trimethyl ammonium chloride, and 0.026 g of initiator ammonium persulfate; mix acrylamide and methacryloyloxyethyl trimethyl ammonium chloride at 400 rpm and stir evenly, introduce nitrogen for 1 hour, then heat to 65°C, and continue stirring to react; dissolve the initiator ammonium persulfate in 16 g of water to obtain an initiator solution, then add the initiator solution dropwise to the reaction solution, continue the reaction for 6 hours, and obtain a crude product; repeatedly wash the crude product with an ethanol / acetone mixture with a volume ratio of 2:1 until the washed liquid is clear, and then dry the product in a vacuum drying oven at 70°C for 72 hours to obtain an organic cationic polymer.

[0053] Preparation Example 2 Preparation of fluorosilane-modified polyurethane organosilicon composite hollow nanospheres

[0054] The polycarbonate diol in the preparation example of this application was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.;

[0055] The catalyst is dibutyltin dilaurate;

[0056] Perfluorooctyltriethoxysilane was purchased from Hubei Xinmingtai Chemical Co., Ltd.

[0057] Preparation Example 2.1

[0058] S1. 5 g of polycarbonate diol was stirred and dehydrated at 100 ° C under vacuum conditions for 2 h, nitrogen was introduced, 0.6 g of dimethylol propionic acid was added, stirred for 25 min, cooled to 40 ° C, 2.5 g of toluene diisocyanate and 0.005 g of catalyst dibutyltin dilaurate were added, and stirred at a constant temperature of 80 ° C for 2 h to obtain a polyurethane dispersion;

[0059] S2. Add a mixed solution of ethanol and water in a volume ratio of 7:12 to the polyurethane dispersion obtained in S1, disperse uniformly by ultrasonication, continue stirring for 1 hour, then heat to 50°C, add 0.4 g of a 30% NaOH solution by mass, stir uniformly, add 114 g of vinyl triethoxysilane, react for 3 hours, centrifuge to obtain a precipitate, wash the precipitate with ethanol and water alternately by centrifugation, and vacuum dry at 50°C for 30 hours to obtain polyurethane silicone composite nanospheres;

[0060] S3. Perfluorooctyltriethoxysilane and ethanol were mixed at a volume ratio of 1:10 to obtain an ethanol solution of perfluorooctyltriethoxysilane; 0.3 g of polyurethane silicone composite nanospheres were dispersed in a mixed solution of ethanol and water, and after ultrasonic dispersion, the temperature was raised to 60°C, 0.24 mL of ammonia water was added, and after 5 minutes, an ethanol solution containing 0.1 mL of perfluorooctyltriethoxysilane was slowly added dropwise. After reacting for 3 hours, 0.8 mL of ammonia water was added again, and the reaction was continued for 10 hours. The product was obtained by centrifugation, and the precipitate was washed alternately by centrifugation with ethanol and water, and then vacuum dried at 50°C for 30 hours to obtain fluorosilane-modified polyurethane silicone composite hollow nanospheres.

[0061] Preparation Example 2.2

[0062] S1. 5 g of polycarbonate diol was stirred and dehydrated at 110 ° C under vacuum conditions for 2.5 h, nitrogen was introduced, 0.7 g of dimethylol propionic acid was added, stirred for 30 min, cooled to 45 ° C, 3 g of toluene diisocyanate and 0.006 g of catalyst dibutyltin dilaurate were added, and stirred at a constant temperature of 85 ° C for 2.5 h to obtain a polyurethane dispersion;

[0063] S2. Add a mixed solution of ethanol and water in a volume ratio of 8:11 to the polyurethane dispersion obtained in S1, and continue stirring for 1.5 hours after ultrasonic dispersion. Then, heat it to 55°C, add 0.45g of a 30% NaOH solution by mass, stir it evenly, and then add 119g of vinyl triethoxysilane. After reacting for 4 hours, centrifuge to obtain a precipitate. Wash the precipitate with ethanol and water alternately by centrifugation, and then vacuum dry it at 55°C for 25 hours to obtain polyurethane silicone composite nanospheres.

[0064] S3. Perfluorooctyltriethoxysilane and ethanol were mixed at a volume ratio of 1:10.5 to obtain an ethanol solution of perfluorooctyltriethoxysilane; 0.4 g of polyurethane silicone composite nanospheres were dispersed in a mixed solution of ethanol and water, and after ultrasonic dispersion, the temperature was raised to 65°C, 0.25 mL of ammonia water was added, and after 6 minutes, an ethanol solution containing 0.2 mL of perfluorooctyltriethoxysilane was slowly added dropwise. After reacting for 3.5 hours, 0.9 mL of ammonia water was added again, and the reaction was continued for 12 hours. The product was obtained by centrifugation, and the precipitate was washed alternately by centrifugation with ethanol and water, and then vacuum dried at 55°C for 25 hours to obtain fluorosilane-modified polyurethane silicone composite hollow nanospheres.

[0065] Preparation Example 2.3

[0066] S1. 5 g of polycarbonate diol was stirred and dehydrated at 100 ° C under vacuum conditions for 3 h, nitrogen was introduced, 0.8 g of dimethylol propionic acid was added, stirred for 35 min, cooled to 50 ° C, 3.5 g of toluene diisocyanate and 0.007 g of catalyst dibutyltin dilaurate were added, and stirred at a constant temperature of 90 ° C for 3 h to obtain a polyurethane dispersion;

[0067] S2. Add a mixed solution of ethanol and water in a volume ratio of 9:10 to the polyurethane dispersion obtained in S1, and after ultrasonic dispersion, continue stirring for 2 hours, then heat to 60°C, add 0.5g of a 30% NaOH solution by mass, stir evenly, add 124g of vinyl triethoxysilane, react for 5 hours, and centrifuge to obtain a precipitate. After washing the precipitate with ethanol and water alternately by centrifugation, vacuum dry at 60°C for 20 hours to obtain polyurethane silicone composite nanospheres;

[0068] S3. Perfluorooctyltriethoxysilane and ethanol were mixed at a volume ratio of 1:11 to obtain an ethanol solution of perfluorooctyltriethoxysilane; 0.5 g of polyurethane silicone composite nanospheres were dispersed in a mixed solution of ethanol and water, and after ultrasonic dispersion, the temperature was raised to 70°C, 0.26 mL of ammonia water was added, and after 7 minutes, an ethanol solution containing 0.3 mL of perfluorooctyltriethoxysilane was slowly added dropwise. After reacting for 4 hours, 1 mL of ammonia water was added again, and the reaction was continued for 14 hours. The product was obtained by centrifugation, and the precipitate was washed alternately by centrifugation with ethanol and water, and then vacuum dried at 60°C for 20 hours to obtain fluorosilane-modified polyurethane silicone composite hollow nanospheres.

[0069] Example

[0070] Example 1

[0071] Weigh 2g of the organic cationic polymer obtained in Preparation Example 1.1, 10g of the cationic surfactant hexadecyltrimethylammonium bromide, 6g of the fluorosilane-modified polyurethane silicone composite hollow nanospheres obtained in Preparation Example 2.1, and 0.8g of a high-performance mineral-based gelling material, mix and stir them evenly at 400rpm for 1h to obtain a clay reinforcing stabilizer.

[0072] Example 2

[0073] Weigh 3g of the organic cationic polymer obtained in Preparation Example 1.1, 12g of the cationic surfactant hexadecyltrimethylammonium bromide, 8g of the fluorosilane-modified polyurethane silicone composite hollow nanospheres obtained in Preparation Example 2.1, and 1.4g of a high-performance mineral-based gelling material, mix and stir them evenly at 350rpm for 2h to obtain a clay reinforcing stabilizer.

[0074] Example 3

[0075] Weigh 4 g of the organic cationic polymer obtained in Preparation Example 1.1, 8 g of the cationic surfactant hexadecyltrimethylammonium bromide, 10 g of the fluorosilane-modified polyurethane silicone composite hollow nanospheres obtained in Preparation Example 2.1, and 2 g of high-performance mineral-based gelling material, mix and stir them evenly at 300 rpm for 3 hours to obtain a clay reinforcing stabilizer.

[0076] Example 4

[0077] The difference between Example 4 and Example 1 is that the cationic surfactant used in Example 4 is coconut oil alkyl trimethyl ammonium chloride, with a mass of 10 g.

[0078] Example 5

[0079] The difference between Example 5 and Example 1 is that the cationic surfactant used in Example 5 is dodecyltrimethylammonium bromide with a mass of 10 g.

[0080] Example 6

[0081] The difference between Example 6 and Example 1 is that the organic cationic polymer used in Example 6 comes from Preparation Example 1.2, with a mass of 2 g.

[0082] Example 7

[0083] The difference between Example 7 and Example 1 is that the organic cationic polymer used in Example 7 comes from Preparation Example 1.3, with a mass of 2 g.

[0084] Example 8

[0085] The difference between Example 8 and Example 1 is that the fluorosilane-modified polyurethane silicone composite hollow nano-microspheres used in Example 8 come from Preparation Example 2.2, with a mass of 2 g.

[0086] Example 9

[0087] The difference between Example 9 and Example 1 is that the fluorosilane-modified polyurethane organosilicon composite hollow nano-microspheres used in Example 9 come from Preparation Example 2.3, with a mass of 2 g.

[0088] Comparative Example

[0089] Comparative Example 1

[0090] Weigh 1 g of the organic cationic polymer obtained in Preparation Example 1.1, 6 g of the cationic surfactant hexadecyltrimethylammonium bromide, 4 g of the fluorosilane-modified polyurethane silicone composite hollow nanospheres obtained in Preparation Example 2.1, and 0.5 g of a high-performance mineral-based gelling material, mix and stir them evenly at 400 rpm for 1 hour to obtain a clay reinforcing stabilizer.

[0091] Comparative Example 2

[0092] Weigh 7g of the organic cationic polymer obtained in Preparation Example 1.1, 14g of the cationic surfactant hexadecyltrimethylammonium bromide, 12g of the fluorosilane-modified polyurethane silicone composite hollow nanospheres obtained in Preparation Example 2.1, and 2.6g of high-performance mineral-based gelling material, mix and stir them evenly at 400rpm for 1h to obtain a clay reinforcing stabilizer.

[0093] Application Examples

[0094] The clay reinforcing stabilizers prepared in Examples 1-9 and Comparative Examples 1-2 were respectively used to prepare Application Examples 1-9 and Comparative Application Examples 1-2 according to the following methods.

[0095] Mix 20g of clay and 0.1g of clay stabilizer, add 2g of water, put into a mold, compact it with a hydraulic molding machine at 50MPa, cure it at room temperature for 2 days, put it into a drying hole at 50℃ for 10 hours, and then dry it at 120℃ for 10 hours to obtain unfired clay bricks.

[0096] Performance testing

[0097] Referring to T / CHTS10103-2023 "Technical Guidelines for Construction of Polymer Stabilized Fine-Grained Soil Base", the compressive strength, water stability and frost resistance of the unfired clay bricks of Example 1-9 and Comparative Application Example 1-2 were tested, and the results are shown in Table 1.

[0098] The specific test results are as follows:

[0099] Table 1 Test results of application examples 1-9 and comparative application examples 1-2

[0100]

[0101]

[0102] It can be seen from the test results in Table 1 that the water stability and frost resistance clay strengthening stabilizer provided in the present application is used in clay, which can effectively improve the water stability and frost resistance of the clay. The water stability coefficient of the unfired clay bricks prepared can reach more than 97%, and the maximum can reach 98.8%, indicating that the clay strengthening stabilizer provided in the present application can effectively improve the waterproof performance of the clay; the freeze-thaw residual compressive strength ratio can also reach more than 90%, among which, in the medium freezing area, the maximum freeze-thaw residual compressive strength ratio can reach 92.7%; in the heavy freezing area, the maximum freeze-thaw residual compressive strength ratio can reach 91.2%, indicating that the clay strengthening stabilizer provided in the present application can effectively improve the frost resistance of the clay.

[0103] It can be seen from the test results of comparative application examples 1-2 that when the raw materials of the clay strengthening stabilizer are outside the weight range, the water stability coefficient and freeze-thaw residual compressive strength ratio of the obtained clay bricks are significantly reduced.

[0104] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. Water stability and frost resistance clay strengthening stabilizer, characterized by: The raw materials are composed of the following substances by weight: 2-4 parts of organic cationic polymer, 8-12 parts of cationic surfactant, 6-10 parts of fluorosilane-modified polyurethane organic silicon composite hollow nano-microspheres, and 0.8-2 parts of high-performance mineral-based gelling material; the mass ratio of the organic cationic polymer to the cationic surfactant is 1:(3-5); The cationic surfactant is one of hexadecyl trimethyl ammonium bromide, coconut oil alkyl trimethyl ammonium chloride and dodecyl trimethyl ammonium bromide; The raw materials of the organic cationic polymer include acrylamide, methacryloyloxyethyl trimethyl ammonium chloride, and an initiator, wherein the molar ratio of acrylamide to methacryloyloxyethyl trimethyl ammonium chloride is (1.8-2.2):1; The initiator is ammonium persulfate, and the content of the initiator is 1%-2%; The method for preparing the fluorosilane-modified polyurethane organic silicon composite hollow nano-microspheres comprises the following steps: The fluorosilane and ethanol are mixed at a volume ratio of 1: (10-11) to obtain an ethanol solution of fluorosilane; 0.3-0.5 parts of polyurethane silicone composite nano-microspheres are dispersed in a mixed solution of ethanol and water, and after uniform ultrasonic dispersion, the temperature is raised to 60-70°C, and ammonia water is added. After 5-7 minutes, an ethanol solution containing 0.1-0.3 mL of fluorosilane is slowly added dropwise, and after reacting for 3-4 hours, ammonia water is added again, and the reaction is continued for 10-14 hours. The product is obtained by centrifugation, and after alternate centrifugation with ethanol and water, it is dried in vacuo at 50-60°C for 20-30 hours to obtain fluorosilane-modified polyurethane silicone composite hollow nano-microspheres; The fluorosilane is perfluorooctyltriethoxysilane; The preparation method of the polyurethane silicone composite nano-microspheres comprises the following steps: S1. 5-7 parts of polycarbonate diol are stirred and dehydrated at 100-120 ° C under vacuum conditions for 2-3h, nitrogen is introduced, 0.6-0.8 parts of dimethylol propionic acid are added, stirred for 25-35min, cooled to 40-50 ° C, 2.5-3.5 parts of toluene diisocyanate and 0.005-0.007 parts of catalyst are added, and stirred at a constant temperature of 80-90 ° C for 2-3h to obtain a polyurethane dispersion; S2. Add a mixed solution of ethanol and water in a volume ratio of (7-9): (10-12) to the polyurethane dispersion obtained in S1, disperse uniformly by ultrasonication, continue stirring for 1-2 hours, then heat to 50-60°C, add NaOH solution, stir uniformly, add 0.6-0.8L of vinyl triethoxysilane, react for 3-5 hours, centrifuge to obtain a precipitate, wash with ethanol and water alternately by centrifugation, and vacuum dry at 50-60°C for 20-30 hours to obtain polyurethane silicone composite nanospheres; The catalyst is dibutyltin dilaurate.

2. The method for preparing the water-stable and frost-resistant clay strengthening stabilizer according to claim 1, characterized in that: The following steps are involved: The organic cationic polymer, the cationic surfactant, the fluorosilane-modified organic silicon nano-microspheres and the high-performance mineral-based gelling material are weighed in parts by weight, mixed and stirred evenly to obtain a clay reinforcing stabilizer.

3. The method for preparing the water-stable and frost-resistant clay strengthening stabilizer according to claim 2, characterized in that: The method for preparing the organic cationic polymer comprises the following steps: Weigh acrylamide, methacryloyloxyethyl trimethyl ammonium chloride and initiator; mix acrylamide and methacryloyloxyethyl trimethyl ammonium chloride and stir them evenly, introduce nitrogen, heat to 55-65° C., and continue stirring; dissolve the initiator in water to obtain an initiator solution, then add the initiator solution dropwise to the reaction solution, continue the reaction for 6-8 hours, and obtain a crude product; wash and dry the crude product to obtain an organic cationic polymer.

4. The use of the water stability and frost resistance clay strengthening stabilizer according to claim 1, characterized in that: The clay strengthening stabilizer is used for preparing unfired clay bricks.

Citation Information

Patent Citations

  • Preparation method of waterborne polyurethane-silicon dioxide nano composite emulsion

    CN105732940A

  • Polymer clay stabilizer for fracturing and preparation method thereof

    CN113912774A